Naẓarīyat al-Fanā’ fī al-Turāth al-Ṣūfī al-Indūnīsī: Dirāsah Taḥlīlīyah - Bidin, Masri Elmahsyar (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2009)
This article attempts to analyze deeply concept of fana' that expanded by Indonesian Sufis such as Hamzah Fansuri and Muhammad Nat'is aI' Banjari, in relation with other Sufis in the Muslim zeroed such as lbnu 'Arabi, Abi Yazid al-Bustami, and al-Ghazali. Connection with Indian philosophy like Nirvana and Yoga will also be explored. In the courses of its development, the concept of fana' has triggered controversies in intellectual community, and even there it yielded some prejudices among them that this concept was religious deviation in the Muslim world. This can be seen for example in the cases of al-Hallaj as he said